2017
DOI: 10.23925/2176-901x.2017v20i1p93-108
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de morbimortalidade e os desafios para a atenção domiciliar do idoso brasileiro

Abstract: Objetivou-se caracterizar o perfil de morbimortalidade e apontar os desafios para a Atenção Domiciliar do idoso brasileiro. Estudo descritivo, com dados secundários, de domínio público. Observou-se aumento no número de idosos, predomínio da morbimortalidade e hospitalizações por doenças crônicas. Nesse contexto, a atenção domiciliar figura como importante alternativa assistencial, mas que tem sido implementada com importantes restrições.Palavras-chave: Idoso; Indicadores de morbimortalidade; Assistência domici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
21

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 5 publications
(11 reference statements)
0
5
0
21
Order By: Relevance
“…In an ever-expanding world, including Brazil (13)(14) , home care is part of a complex context, since patients treated in this environment tend to be older, have a greater number of comorbidities and disabilities, as well as several medical prescriptions, which fragment care. Moreover, such a care context requires an increasing use of previously used hospital technologies, which is associated with a higher risk of errors and adverse events (11,13,15) .…”
Section: Introductionmentioning
confidence: 99%
“…In an ever-expanding world, including Brazil (13)(14) , home care is part of a complex context, since patients treated in this environment tend to be older, have a greater number of comorbidities and disabilities, as well as several medical prescriptions, which fragment care. Moreover, such a care context requires an increasing use of previously used hospital technologies, which is associated with a higher risk of errors and adverse events (11,13,15) .…”
Section: Introductionmentioning
confidence: 99%
“…The desire to increase life expectancy has always been a desire present in different societies, and the change in the age pyramid has already shown that there is an increase, in absolute and relative terms, in the number of elderly people. Both in Brazil and in other countries, implications have been observed that go beyond changes in the demographic picture -for example, important changes in the epidemiological panorama, particularly due to the exponential increase in Chronic Non-communicable Diseases (CNCDs) (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Nesse contexto, tanto no Brasil como em outros países, tem-se percebido que as implicações vão além das alterações do quadro demográfico, tornando-se salutar a atenção acerca das importantes modificações no panorama epidemiológico, em virtude do aumento das Doenças Crônicas Não Transmissíveis (DCNT) (2) . Contudo, a idade cronológica não deve ser considerada um marcador preciso para as mudanças que acompanham o envelhecimento, já que existem diferenças relacionadas ao estado de saúde, bem como o contexto multifatorial em que a pessoa idosa se encontra (1) .…”
Section: Introductionunclassified